2015
DOI: 10.1016/j.wombi.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Supporting women to achieve breastfeeding to six months postpartum – The theoretical foundations of a successful program

Abstract: . (2015). Supporting women to achieve breastfeeding to six months postpartum -The theoretical foundations of a successful program. Women and Birth, 28 (4), 265-271. Supporting women to achieve breastfeeding to six months postpartumThe theoretical foundations of a successful program AbstractBackground Although the benefits of breastfeeding to six months are well-established, only about half of Australian women succeed. The factors associated with successful breastfeeding are rarely translated into effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 41 publications
0
11
0
1
Order By: Relevance
“…Existe evidencia que señala que las intervenciones que empoderan a las madres en la toma de decisiones con respecto a su lactancia, les permiten identificar por sí mismas sus problemas, con lo cual son capaces de poner en práctica estrategias de solución a éstos. Además, se enfatiza la importancia de considerar, en el establecimiento de la relación profesional-usuaria, el respeto por su condición de género y nueva madre, estableciendo una relación horizontal, libre de prejuicios, respetando los tiempos individuales y basada en la confianza [26][27][28] . De acuerdo a los resultados de este y otros estudios, se concluye que el período de mayor vulnerabilidad para la mujer y su hijo, en relación a la instalación de la lactancia, corresponde a las primeras semanas post parto.…”
Section: Discussionunclassified
“…Existe evidencia que señala que las intervenciones que empoderan a las madres en la toma de decisiones con respecto a su lactancia, les permiten identificar por sí mismas sus problemas, con lo cual son capaces de poner en práctica estrategias de solución a éstos. Además, se enfatiza la importancia de considerar, en el establecimiento de la relación profesional-usuaria, el respeto por su condición de género y nueva madre, estableciendo una relación horizontal, libre de prejuicios, respetando los tiempos individuales y basada en la confianza [26][27][28] . De acuerdo a los resultados de este y otros estudios, se concluye que el período de mayor vulnerabilidad para la mujer y su hijo, en relación a la instalación de la lactancia, corresponde a las primeras semanas post parto.…”
Section: Discussionunclassified
“…When individuals are happy, relaxed and calm (physiological and affective states) they may achieve higher self-efficacy [ 26 28 ]. It has been suggested that social and professional support should include help for mothers to relax and focus on their feelings of closeness with their infant [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Although considered natural and instinctive, BF can be affected by numerous biological, social, historical and cultural factors. [10][11][12] According to Scavenius et al 12 social constraints in relation to BF may develop, leading to decreased suckling and eventually to the cessation of BF.…”
Section: Introductionmentioning
confidence: 99%